Excessive testosterone treatment and castration induce reactive astrocytes and fos immunoreactivity in suprachiasmatic nucleus of mice - Satriotomo, Irawan; Miki, Takanori; Gonzalez, Daniel; Matsumoto, Yoshiki; Li, Hong-Peng; Gu, He; Takeuchi, Yoshiki (Brain Research, 2004)
The suprachiasmatic nucleus (SCN) has long been recognized as the central mammalian circadian pacemaker that controls behavioral and physiological processes. The role of the SCN in circadian rhythms has been the subject of a wide range of physiological and behavioral studies, although the influence of homeostasis rhythms (such as fluctuating hormone levels) on the SCN of the hypothalamus is not entirely clear. The present study was undertaken to examine the morphological interactions between astroglial and neuronal elements in the SCN of mice after either a short-term excessive testosterone treatment (ETT) or castration, using glial fibrillary acidic protein (GFAP), and immediate early gene c- fos as well as calbindin-D28k (CB) immunohistochemistry. Both ETT and castration resulted in a significant increase in the accumulation of reactive astrocytes and Fos-imunoreactivity (IR), especially in the dorsomedial (DM) sub-region of the SCN. However, CB-IR neurons in the examined brain regions showed little change. These findings indicate that the DM sub-region of the SCN may be a possible center of hormonal regulation via a hypothalamic neuroendocrine circuit, and that a non-photic stimuli mechanism might play a role in circadian rhythm regulation.